Hyperdoping of silicon films with titanium via nanosecond-laser melting: Structure evolution, impurity distribution, sub-bandgap formation, and doping mechanism. (March 2022) - Wen, C.; Shi, Z.Q.; Wang, J.X.; Tang, J.L.; Zhang, Y.B.; Jiang, Y.; Ma, Y.J.; Li, X.H.; Yang, W.B.
Highlights: Hyperdoping of Si films with Ti via ns-laser melting replaces conventional hyperdoping of Si wafer. ∼ 90% Vis-NIR absorptance, good electronic transport, and μm-level thickness are achieved. Film structure exhibits the crystallinity of ∼ 70% and nanocrystal size of 10–50 nm. Ti impurity band is formed with two sub-bandgaps of energy 385–448 and 759 meV. Doping processes include material ejection, ablation, redeposition, melting, and crystallization. Abstract: Hyperdoping of Si films with Ti was achieved via nanosecond (ns)-laser melting of Si/Ti composite films under different film deposition and laser treatment conditions. The structural evolution (from amorphous to nanocrystalline structure), Ti impurity distribution and concentration variation, and sub-bandgap (Ti impurity band) formation in the films, were carefully studied to optimize the hyperdoping process. The results show that the hyperdoping concentration and depth can be manipulated by controlling the Si and Ti co-evaporation speed ratio, Si/Ti composite film thickness together with a matched ns-laser fluence. Furthermore, Ti impurity bands were determined with two sub-bandgaps of energy 385–448 and 759 meV. In addition, the mechanism of ns-laser hyperdoping of Si films was clarified into the heat transfer, material ejection, partial ablation and redeposition, melting, and nanocrystallization (simultaneous hyperdoping) processes. Thus, hyperdoped nanocrystalline films up to the micron-level thickness with a crystallinity of ∼ 70%, an optical absorptance of ∼ 90% from the visible to the long-wavelength near-infrared spectrum, and good electronic transport properties were obtained. These hyperdoped Si films exhibit a high potential in the development of Si-based broad-spectrum tandem or thin film solar cells and room-temperature infrared photodetectors.